PEMANFAATAN TEKNOLOGI CERDAS DALAM URBAN FARMING: TINJAUAN LITERATUR ATAS PERAN SENSOR, IRIGASI OTOMATIS, DAN MANAJEMEN LIMBAH ORGANIK - Rita Hayati; Al-Amin (Jurnal Salome : Multidisipliner Keilmuan, 2025)
Urban farming is a strategic solution to address food security and environmental challenges in densely populated urban areas with limited land. This study aims to examine the application of smart technology in urban farming through a literature review, with a focus on the role of sensors, automatic irrigation systems, and organic waste management. The study findings indicate that sensor integration enables real-time monitoring of plant conditions, allowing for precise and efficient interventions. Automatic irrigation systems based on sensors and the Internet of Things (IoT) have proven effective in reducing water usage and increasing crop productivity. Additionally, organic waste management through composting and liquid fertilisers supports sustainable agricultural cycles and reduces urban waste volume. Despite challenges such as initial investment costs, limited knowledge, and infrastructure requirements, the potential for developing technology-based urban farming is significant with cross-sector collaboration. Thus, the utilisation of smart technology in urban farming can serve as an innovative solution to create an efficient, productive, and environmentally friendly urban agricultural system.